Mengukur Pengaruh Kualitas Pelayanan Terhadap Kepuasan dan Loyalitas Pengguna Perpustakaan UMS - Ryan Agung Pangestu; Anton Agus Setyawan (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
This research aims to evaluate the impact or effects of effect of Service, information control, and the Library as a Place on the satisfaction and loyalty of library users. The samples in this test were active students and users who utilized library services at the Muhammadiyah University of Surakarta. Sampling was done using a purposive sampling technique to obtain a total of 150 respondents. The data management is carried out using the SmartPLS 3.0 statistical calculation tool and it can be stated that the effect of Service, Information Control, and Library as Place has a significant effect and has a positive impact on user satisfaction and loyalty so the hypothesis can be accepted.